Advances in Pseudo-Differential Operators 2004
DOI: 10.1007/978-3-0348-7840-1_8
|View full text |Cite
|
Sign up to set email alerts
|

Localization Operators Via Time-Frequency Analysis

Abstract: Abstract. A systematic overview of localization operators using a time-frequency approach is given. Sufficient and necessary regularity results for localization operators with symbols and windows living in various function spaces (such as L p or modulation spaces) are discussed. Finally, an exact and an asymptotic product formulae are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Detailed studies of the interaction of both regularizations and localizations, can be found for example in [49,53,54,77] and in engineering literature, we encounter these interactions in terms of the interplay between "windowing" on one hand and "interpolation" on the other. An equivalent is the so-called "zero-padding" technique (e.g.…”
Section: A Regularization-localization Dualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed studies of the interaction of both regularizations and localizations, can be found for example in [49,53,54,77] and in engineering literature, we encounter these interactions in terms of the interplay between "windowing" on one hand and "interpolation" on the other. An equivalent is the so-called "zero-padding" technique (e.g.…”
Section: A Regularization-localization Dualitymentioning
confidence: 99%
“…It culminated, however, in the term "localization operator". It appears in 1988 for the first time (see [53], p. 133 in [54]) in Daubechies' article [55] and later in Daubechies' 1992 standard textbook [52]. Meanwhile, "localizations" occur in many publications [2,52,[54][55][56][57][58][59][60][61][62][63], amongst others as "localized trigonometric functions" or "localized sine basis" [52,57,64], as "localized frames" [65], "local trigonometric bases", as "local representations" [6] or simply in terms of "locally integrable" functions.…”
mentioning
confidence: 99%
“…If g(t) = γ(t) = e −πt 2 , then M g,γ,λ is the classical Anti-Wick operator. M g,γ,λ was investigated in many papers, such as Berezin [1], Shubin [25], Wong [29], Feichtinger and Nowak [13], Boggiato, Cordero, Gröchenig, Tabacco [2,4,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%